Analysis of Effect of Price And Quality Products Buying Decision Against Honda Motorcycle At PT. xyz - Suci Lestari Siregar (Enrichment : Journal of Management, 2019)
This study aims to determine the "Effect of Price and Quality of Products on purchasing decisions at PT Honda motorcycles. Rotella Mandiri Persada Lubukpakam". The sample used in this study is that consumers PT. Rotella Lubukpakam Mandiri Persada. The number of samples is calculated using the theory suparmono and hariyanto then didapatlah total sample of 80 people. The results showed that the independent variables, namely haraga (X1) a negative effect on purchasing decisions motorcycle Honda (Y) it can be seen from the t-test value of -0.420 with a significance value of 0.675 is greater than 0.05 and product quality (X2) has positive and significant influence on purchasing decisions at PT Honda motorcycles. Rotella Lubukpakam Mandiri Persada.